ATP secretion in the male reproductive tract: essential role of CFTR - Ruan, Ye Chun (Blackwell Science Inc, 2012)
Extracellular ATP is essential for the function of the epididymis and spermatozoa, but ATP release in the epididymis remains uncharacterized. We investigated here whether epithelial cells release ATP into the lumen of the epididymis, and we examined the role of the cystic fibrosis transmembrane conductance regulator (CFTR), a Cl(−) and HCO(3)(−) conducting ion channel known to be associated with male fertility, in this process. Immunofluorescence labelling of mouse cauda epididymidis showed expression of CFTR in principal cells but not in other epithelial cells. CFTR mRNA was not detectable in clear cells isolated by fluorescence-activated cell sorting (FACS) from B1-EGFP mice, which express enhanced green fluorescent protein (EGFP) exclusively in these cells in the epididymis. ATP release was detected from the mouse epididymal principal cell line (DC2) and increased by adrenaline and forskolin. Inhibition of CFTR with CFTR(inh172) and transfection with CFTR-specific siRNAs in DC2 cells reduced basal and forskolin-activated ATP release. CFTR-dependent ATP release was also observed in primary cultures of mouse epididymal epithelial cells. In addition, steady-state ATP release was detected in vivo in mice, by measuring ATP concentration in a solution perfused through the lumen of the cauda epididymidis tubule and collected by cannulation of the vas deferens. Luminal CFTR(inh172) reduced the ATP concentration detected in the perfusate. This study shows that CFTR is involved in the regulation of ATP release from principal cells in the cauda epididymidis. Given that mutations in CFTR are a leading cause of male infertility, we propose that defective ATP signalling in the epididymis might contribute to dysfunction of the male reproductive tract associated with these mutations.